Improving the performance of PERC silicon solar cells by optimizing the surface inverted pyramid structure on large-area mono-crystalline silicon wafers. (February 2022) - Zhang, Danni; Wang, Longjie; Jia, Rui; Tao, Ke; Jiang, Shuai; Ge, Huayun; Wang, Bolong; Gao, Zhibo; Li, Xinpu; Li, Minghui; Jin, Zhi
Abstract: Optimizing the surface texture of silicon wafer to improve the light trapping performance and effective carrier lifetime of silicon surface is an efficient and low-cost way to enhance the energy conversion efficiency of mono-crystalline silicon PERC solar cells. In this paper, a simple method was adopted to prepare inverted pyramids with different sizes by varying the ρ value (ρ = [HF]/([HF]+[H2 O2 ]) of Cu metal assisted chemical etching (Cu-MACE) etching solution. The chemical mechanism of formation, etching rate, surface reflectivity, and effective minority carrier lifetime mapping of different silicon surface structures were systematically investigated. Moreover, the solar energy absorption rate of these different surface structures were studied by the finite difference time domain (FDTD) method. The results show that when the ρ value was between 25% and 90%, the etching rate of Cu nanoparticles increases with increasing ρ value. The final results reveal that the surface reflectivity, effective minority carrier lifetime and the light absorption were optimal when ρ∼75%, and the uniformity of corresponding inverted pyramid texture is the best. By utilizing the best inverted pyramid texture, the highest efficiency is 22.69%, corresponding Voc is 680.42 mV, Jsc is 41.20 mA/cm 2, and FF is 80.94% on the 156.75 × 156.75 mm 2 for large area mono-crystalline silicon PERC solar cell. Highlights: The optimized inverted pyramid structure were obtained. The efficiency of such mono-Si PERC solar cells reached 22.68%. The weighted average reflectance can be as low as 5.45%. Various inverted pyramid structures prepared by a simple method. FDTD solution were performed to evaluate the light absorption of different structural parameters.